2006
DOI: 10.1002/asl.131
|View full text |Cite
|
Sign up to set email alerts
|

Total rain accumulation and rain‐rate analysis for small tropical Pacific islands: a case study of Suva, Fiji

Abstract: Rain-rate analyses using hourly data from 1990 to 2002 predict rain occurrence for ∼15% of the year while minute data for the period Apr '02-Mar '03 resolve rain-rate more accurately and show rain occurrence of ∼2% of the year. It is estimated that <1% of the rain at the site is mainly convective. Rainfall analysis confirms its dependence on El Niño Southern Oscillation and convergence zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Though the SPCZ lies mostly over the South Pacific Ocean, there are many small island states that depend on its rainfall (e.g. Griffiths et al, ; Kumar et al, ). Small displacements in its location have resulted in severe droughts and floods across the region (Cai et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the SPCZ lies mostly over the South Pacific Ocean, there are many small island states that depend on its rainfall (e.g. Griffiths et al, ; Kumar et al, ). Small displacements in its location have resulted in severe droughts and floods across the region (Cai et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Though the SPCZ lies mostly over the South Pacific Ocean, there are many small island states that depend on its rainfall (e.g. Griffiths et al, 2003;Kumar et al, 2006). Small displacements (a) (b) (c) Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its strong rainfall gradient, a small displacement in the position of the SPCZ causes drastic changes to hydroclimatic conditions and the frequency of extreme weather events-such as droughts, floods and tropical cyclones-experienced by vulnerable island countries in the region [1][2][3][4][5][6][7] . The SPCZ position varies from its climatological mean location with the El Niño/ Southern Oscillation (ENSO), moving a few degrees northward during moderate El Niño events and southward during La Niña events 2,5,6 .…”
mentioning
confidence: 99%
“…Marked differences were observed in the lightning activity between the two seasons, carried out using the Lightning Imaging Sensor satellite data and ground based WWLLN measurements (Ramachandran et al, 2005). Likewise, long-term rainfall studies at Suva also revealed distinct seasonal dependence (Kumar et al, 2006). In Fig.…”
Section: Comparison With Global Trendsmentioning
confidence: 82%